Formulation of Red Snapper (Lutjanus campechanus) Pempek with Chayote (Sechium edule) Puree and Its Effect on Chemical and Sensory Characteristics - Alhanannasir Alhanannasir; Dasir Dasir; Delly Efriani (Universitas Muhammadiyah Palembang, 2026)
Pempek is a regional specialty from Palembang City, South Sumatra Province, made from fish, tapioca flour, water, and salt. This study was to evaluate the effect of the addition of chayote puree on the chemical and organoleptic properties of red snapper pempek. The method used is quantitatively using a Randomized Group Design (RAK) arranged in a Non Factorial manner with five treatments, namely L1 (addition of 5% chayote puree), L2 (addition of chayote puree 10% of the total ingredients), L3 (addition of chayote puree 15% of the total ingredients), L4 (addition of chayote puree 20% of the total ingredients), and L5 (addition of chayote puree 25% of the total ingredients), repeated three times. The parameters observed included protein and fiber content, while the hedonic test assessed color, aroma, taste, and texture. The findings showed that adding chayote puree had a highly significant effect on protein and fiber content. The highest protein content was found in treatment L5 (±18.50%), and the lowest was in treatment L1 (±14.75%). The highest fiber content was in treatment L5 (±22.01%), and the lowest was in treatment L1 (±9.67%). Moderately preferred treatment L1 (5%) with color characteristics ±3.96 and taste ±3.88. Moderately preferred treatment L3 (15%) with aroma characteristics ±3.76. Moderately preferred treatment L5 (25%) with chewiness characteristics ± 3.48.